Effects of fiber type, volume fraction and aspect ratio on the flexural and acoustic emission behaviors of steel fiber reinforced concrete. (30th August 2018) - Li, Biao; Xu, Lihua; Shi, Yuchuan; Chi, Yin; Liu, Qi; Li, Changning
Highlights: Effects of fiber parameters on the flexural and AE behaviors of SFRC were investigated. The flexural strength, toughness, fracture process and failure mode of SFRC was studied. The reinforcing mechanism of steel fiber with various fiber parameters was analyzed. Abstract: This paper investigates the effects of fiber type, volume fraction and aspect ratio on the flexural and acoustic emission (AE) behaviors of steel fiber reinforced concrete (SFRC) using four-point bending tests. Three types of steel fibers, i.e., straight, hooked-end and corrugated fiber, four volume fractions of 0.5%, 1.0%, 1.5% and 2.0%, three corrugated fiber aspect ratios of 40, 60 and 80, were respectively selected. The flexural behavior of SFRC in terms of load-deflection curve, ultimate flexural load and toughness was studied. The AE parameters with respect to AE events, average frequency, RA value etc. were used to describe the fracture process and fracture mode of SFRC. The results showed that the flexural and AE behaviors of SFRC vary with various fiber types, volume fractions and aspect ratios. Hooked-end SFRC owns the best flexural behavior. Compared to plain concrete, the ultimate flexural strengths of specimens are maximally improved by 74.29%, 165.07% and 112.65% for straight, hooked-end and corrugated fibers, respectively. The peak load, deflection and toughness of concrete increase with increasing fiber volume fraction and aspect ratio. It is noted from AE results that the cumulative AE events, shear cracks and AE source location points mainly induced by fiber pull-out and sliding increase with the increase of fiber volume fraction and aspect ratio. Hooked-end SFRC has the largest AE events, shear cracks and the amount of scatter points for all the four fiber volume fractions owing to the large amount of fibers sustaining the load at cracks and the good bond performance of hook-end steel fiber and concrete matrix. Moreover, the failure of plain concrete is dominated by tensile cracks, and that is changing to shear cracks with increasing fiber volume fraction.